Mechanical Compression of Coverslipped Tissue Sections During Heat-induced Antigen Retrieval Prevents Section Detachment and Preserves Tissue Morphology. (June 2019) - Eckhard, Andreas H.; O'Malley, Jennifer T.; Nadol, Joseph B.; Adams, Joe C.
Heat-induced antigen retrieval (HIAR) is routinely employed on aldehyde-fixed tissue sections to enhance the reactivity of antibodies that exhibit weak or no specific interactions with tissue antigens when applied in conventional immunohistochemical protocols. A major drawback of HIAR protocols is, however, the heat-induced detachment of sections from the microscope slide with resultant impaired tissue morphology or loss of the section. We developed a method in which tissue sections mounted on glass slides are temporally coverslipped, and a clamp is used to compress the sections on the microscope slide during HIAR treatment. This "pressurized coverslipping" during HIAR was tested on various formalin-fixed tissues (murine kidneys and temporal bones, human tonsils and temporal bones) that were embedded in paraffin or celloidin. The method reliably kept the sections adherent to the slide, preserved the tissue morphology, and effectively retrieved tissue antigens for improved results in immunohistochemical labeling, even for exceptionally delicate, large, and poorly adhering sections, that is, decalcified human temporal bone sections. In summary, we present a simple method for improved slide adherence and morphological preservation of tissue sections during HIAR treatment that can be combined with all HIAR protocols and that requires only basic lab equipment.